Comparative genomics reveals low levels of inter- and intraspecies diversity in the causal agents of dwarf and common bunt of wheat and hint at conspecificity of Tilletia caries and T. laevis - Somayyeh Sedaghatjoo; Bagdevi Mishra; Monika K. Forster; Yvonne Becker; Jens Keilwagen; Berta Killermann; Marco Thines; Petr Karlovsky; Wolfgang Maier (IMA Fungus)
Abstract Tilletia caries and T. laevis, which are the causal agents of common bunt, as well as T. controversa, which causes dwarf bunt of wheat, threaten especially organic wheat farming. The three closely related fungal species differ in their teliospore morphology and partially in their physiology and infection biology. The gene content as well as intraspecies variation in these species and the genetic basis of their separation is unknown. We sequenced the genome of four T. caries, five T. controversa, and two T. laevis and extended this dataset with five publicly available ones. The genomes of the three species displayed microsynteny with up to 94.3% pairwise aligned regions excluding repetitive regions. The majority of functionally characterized genes involved in pathogenicity, life cycle, and infection of corn smut, Ustilago maydis, were found to be absent or poorly conserved in the draft genomes and the biosynthetic pathway for trimethylamine in Tilletia spp. could be different from bacteria. Overall, 75% of the identified protein-coding genes comprising 84% of the total predicted carbohydrate utilizing enzymes, 72.5% putatively secreted proteins, and 47.4% of effector-like proteins were conserved and shared across all 16 isolates. We predicted nine highly identical secondary metabolite biosynthesis gene clusters comprising in total 62 genes in all species and none were species-specific. Less than 0.1% of the protein-coding genes were species-specific and their function remained mostly unknown. Tilletia controversa had the highest intraspecies genetic variation, followed by T. caries and the lowest in T. laevis. Although the genomes of the three species are very similar, employing 241 single copy genes T. controversa was phylogenetically distinct from T. caries and T. laevis, however these two could not be resolved as individual monophyletic groups. This was in line with the genome-wide number of single nucleotide polymorphisms and small insertions and deletions. Despite the conspicuously different teliospore ornamentation of T. caries and T. laevis, a high degree of genomic identity and scarcity of species-specific genes indicate that the two species could be conspecific.